Dimensions of Relationship Marketing and Its Impact on Brand Equity in Banking Industry (Case of Hekmat Iranian Bank) - Mahmood Mohammadian; Amir Aslani Afrashteh (مدیریت مهندسی و رایانش نرم)
One of the new concepts in the field of marketing that was developed after the traditional marketing is relationship marketing. Considering the mutual benefits of both parties (service providers and customers), service organizations such as banks and financial institutions can implement relationship marketing tools and tactics, in order to establish and maintain a long-term relationship with their customers that can help enhance brand equity. The current study discusses the impact of the dimensions of relationship marketing including trust, empathy, bonding, shared values, reciprocity and communication on brand equity consisting of brand loyalty, perceived quality and brand image. This study is an applied research regarding its objectives. Considering the data collection method, it is a descriptive survey which uses structural equation modelling. The statistical population of this researchconsists of the customers of Hekmat Iranian Bank in Tehran. The customers are those who have active accounts in Hekmat Iranian Bank (current and savings accounts). A total number of 390 questionnaires were distributed in order to collect data. The collected information were analysed using SPSS and AMOS 23. The results indicate that trust, empathy, reciprocity and communication have a significant positive effect on banks’ brand equity. Moreover, the results show that shared values and bonding do not have a positive significant effect on banks’ brand equity.